Comparison of the Effect of the Eight-week Corrective Exercises Program, Postural Reeducation, and Combined Training on Women With Upper Cross Syndrome: With Emphasis On Physical Distance Conditions - Bahareh Khosrojerdi; Mohammad Karimizadeh Ardakani; Karim Khalaghi BirakOlia (Shahid Beheshti University of Medical Sciences, 2022)
Background and Aims: Upper cross syndrome is a type of muscle-skeletal disorder that leads to shortening of the anterior muscles and weakness of the posterior muscles at the neck and thorax. One of the common methods of correcting these malalignments is corrective exercises. So far, different approaches have been used to correct this malalignment. Given the physical distance during epidemics and the lack of participation in correctional programs, it is not known whether distance training approaches can be as effective as face-to-face training.Methods: The present study was semi-experimental with a pre-test and post-test design. In the present study, 60 female employees were selected and assigned to four groups randomly. The first experimental group performed corrective exercises, the second experimental group performed postural reeducation training at home during the same period of the training program, the third group performed combination exercises, and the fourth group was considered as control. Before and after the intervention of the forward head angle, the kyphosis and rounded shoulders of the individuals were measured. One-way analysis of variance and paired t-test were used to analyze the data.Results: All three experimental groups showed a significant difference before and after the intervention on the forward head angle, kyphosis, and rounded shoulder (P˂0.05). The results also showed that the rate of improvement in the combined training group was higher than that of the two training groups.Conclusion: According to the test of research hypotheses on the effectiveness of corrective exercise and postural reeducation training on the upper cross syndrome, probably combined exercises are more effective than independent corrective and postural reeducation training. Therefore, it is recommended to trainers and corrective exercise specialists that correctional exercises not be limited to the clinical environment and they can be combined with postural reeducation training at home to get better results.